A checklist of the Caddisflies (Insecta: Trichoptera) from the Yintiaoling Nature Reserve of China, with description of one new species - Peng, Lang; Ge, Xin-Yu; Lu, Qian-Le; Sun, Chang-Hai (Zootaxa, 2025)
A checklist of trichopteran species in Yintiaoling Nature Reserve of China is compiled for the first time. Based on the collected material, 24 species from 15 families are recorded, among which, a new species, Molannodes wuxiensis Peng & Sun, sp. nov., is described. In addition, two other species, Kisaura borealis (Kuhara, 1999) and Apsilochorema nilgiri Mey, 1999 are new to the Chinese fauna and 21 species are newly recorded species for Chongqing. The new species is described, illustrated, and diagnosed, and habitus photographs of most of the recorded species are provided.